Bandwidth enhanced compact PIFA for dual band operation - Agarwal M.; Meshram M.K. (My University, 2025)
In this paper, a compact planar inverted-F antenna element with enhanced bandwidth is proposed. The proposed antenna covers the major communication bands covering a frequency range of 1.826 GHz to 2.489 GHz and 5.714 GHz to 5.890 GHz (with reference to 2:1 VSWR). The proposed antenna element fits in a small volume of 20 × 10 × 0.8 mm3 over the ground plane. To enhance the bandwidth, techniques like slit on the ground plane and parasitic elements are used. The simulated and measured reflection coefficient results are found in good agreement. The radiation pattern, total efficiency, and antenna gain are also presented. © 2015 Radio Society (Mauritius).